The Catalogue of Manuscripts in the Institute of Alevi-Bektashi Culture’s Archive I - Ceylan, Ömür; Ersal, Mehmet (Journal of Alevism-Bektashism Studies, 2019)
The Institute of Alevi-Bektashi Culture was founded in Cologne, Germany, in 1997 under the honorary presidency of Prof. Dr. Irene Melikoff with the goal to conduct scientific, cultural and religious studies on Alevism and Bektashism. The main mission of the Institute of Alevi-Bektashi Culture is “to carry into future the Alevi-Bektashi belief system by preserving its intellectual, historical and religious line and to research it scientifically”. In this context, the Institute of Alevi-Bektashi Culture, since its foundation, has carried out scientific, cultural and religious activities in accordance with its founding purpose. Within the same framework, the Institute organizes symposiums, panels, conferences, workshops and seminars in the scientific field, publishes books and an academic peer-reviewed journal, entitled Journal of Alevism-Bektashism Studies, covered by international indexes.One of the most important scientific accumulations of the Institute is a library containing a special archive on Alevism. The Institute’s library consists of a manuscript archive, printed works on Alevism and a digital archive. Manuscripts and documents obtained from the personal archives of Alevi-Bektashis, a copy of the digital archive of written and visual materials from the Haji Bektashi Veli Research Centre, Gazi University, and a digital archive of data collected in field works by Ayhan Aydin are in the library of the Institute of Alevi-Bektashi Culture. The authors of this paper have started to determine and classify manuscripts from this library since February, 2019. During the analysis of the scripts, they recorded their digital copies by creating information forms. Planed as the first of a series of papers, this paper aims to present the entire corpus of manuscripts (if available- copyright date and record, if available- copy date and record, material condition, structural features, content information, etc.) that belong to the Institute to the science world.An important part of the manuscripts in the Institute’s archive are the scripts donated to the Institute by Mehmet Yaman’s family. After the analysis of these manuscripts, it appears that it is a personal archive gathered from different places inhabited by Alevi communities, especially from the Erzincan region. Apart from Yaman’s personal archive, there are separate manuscripts donated to the Institute’s library by Alevi individuals. The authors of all manuscripts are members of Alevi-Bektashi communities. It can be easily said that the manuscripts are accepted as sacred texts by the belief system. An important part of these manuscripts are “conks”. Considering the length of the paper, its authors considered appropriate to present thirty manuscripts in this paper.
Keywords: the Institute of Alevi-Bektashi Culture; manuscript; the Institute of Alevi-Bektashi Culture’s catalogue of manuscripts; Mehmet Yaman’s collection; “conk”